IMPLEMENTATION OF MATHEMATIC VALUES OF KARAPAN SAPI’S MADURA WITH STAD LEARNING SETTINGS IN SDN PADEMAWU - Harfin Lanya; Chairul Fajar Tafrilyanto; Zumrotun Aini; Sri Indriati Hasanah (Pi: Mathematics Education Journal, 2020)
This research is a Classroom Action Research (PTK) at SDN Pademawu on the subject of flat wakes. Based on field observations, subject teachers do not relate the concept of learning to everyday life which is very important in the process of concept absorption by students and local culture, in this case the culture of the cow karapan. Therefore, it is necessary to implement the implementation of the mathematical values ​​of the Madura cow karapan by setting the STAD (Student Teams Achievement Division) learning model. This research was conducted in two cycles with each stage: planning, implementing, observing, and reflecting. The results of data analysis showed that student activity from cycle I to cycle II had increased from an average of 2.82 to 3.54 in the very good category. While the student response has increased with the value of the student response questionnaire having an average of 83.63% to 96.97% in the positive category. Then based on the test results, the data showed an increase in the proportion of 57.58% to 90.91%.